2018
DOI: 10.1159/000495819
|View full text |Cite
|
Sign up to set email alerts
|

Renal Functions and Prognosis Stratification in Chronic Heart Failure Patients and the Importance of Neutrophil Gelatinase-Associated Lipocalin

Abstract: Background/Aims: The rate of incidence and prevalence of acute kidney injury is increasing due to an increased number of patients with heart failure. Therefore it is very pertinent to early detect the level of renal injuries and to make necessary heart failure predictions. Thus the aim of this study is to determine renal functions and prognosis stratification in chronic heart failure patients and importance of Neutrophil Gelatinase-Associated Lipocalin (NGAL), an early diagnostic marker of acute kidney injury,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 27 publications
0
7
0
2
Order By: Relevance
“…NGAL is increased in chronic renal injury. 27,28,29 If NGAL is elevated, there is more tubular production, as several authors have demonstrated, or because there is less tubular reabsorption, as has just been shown by Sancho-Martínez et al 29,30 Two urinary markers of kidney damage -NGAL and NAG -were lower in GA than GB both at the beginning and at the end of the study. These data are new: until now, it has not been described that the elderly with RUTI had these higher urine markers.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…NGAL is increased in chronic renal injury. 27,28,29 If NGAL is elevated, there is more tubular production, as several authors have demonstrated, or because there is less tubular reabsorption, as has just been shown by Sancho-Martínez et al 29,30 Two urinary markers of kidney damage -NGAL and NAG -were lower in GA than GB both at the beginning and at the end of the study. These data are new: until now, it has not been described that the elderly with RUTI had these higher urine markers.…”
Section: Discussionmentioning
confidence: 78%
“…NGAL is increased in chronic renal injury. 27,28,29 If NGAL is elevated, there is more tubular production, as several authors have demonstrated, or because there is less tubular reabsorption, as has just been shown by Sancho-Martínez et al 29,30…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…We hypothesized that elevated tubule damage markers at discharge -which represent residual tubular cell stress caused by pathogenic mechanisms (e.g., neurohumoral activation) or therapeutical efforts, are independent factors related to worse outcomes following an ADHF episode. Elevated urine NGAL has previously been linked to poorer outcomes in a variety of clinical settings, including CHF (GISSI-HF study) [31,32] and chronic kidney disease (CKD; CRIC study) [33]. Increased urine NGAL also appears to be a mortality risk factor in the elderly [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…цев, но может быть предиктором сердечно-сосудистых событий у пациентов с хронической болезнью почек [5]. Исследования последних лет также показали, что уровень NGAL, связанный с NT-proBNP, был предиктором сердечно-сосудистых событий и смертности у пациентов с ХСН [14]. При этом исследователи показали, что уровень NGAL был выше у гипертоников.…”
Section: материал и методыunclassified